Tiger snakes, Notechis scutatus, as a Bioindicator of Wetland Health across the urban matrix of Perth, Western Australia - Lettoof, Damian Christopher (Curtin University, 2021)
Urbanisation frequently degrades wetlands via physical modifications, novel stressors and the introduction of pollutants. The health of wetlands can be measured through the use of bioindicators - such as top predators. The research in this thesis quantifies a suite of contaminants and health parameters in snake populations throughout an urban matrix, assesses patterns of bioaccumulation, parasitism and population genomics on snake health, and concludes tiger snakes can be used as an appropriate bioindicator species.